Peran Media Sosial dalam Pemasaran Event di Mal Botani Square - Handayani, Fika; Setyawan, Heri (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2024)
The study examines the role of social media in event marketing at the Botani Square Mall, focusing on mutual engagement between social media use and event management. In today’s digital age, social media has become a vital medium for increasing consumer participation and engagement. The study evaluated the effectiveness of marketing strategies implemented by Botani Square Mall in promoting events organized through social media to their impact on the event organized. Maintenance of an event requires social media to be able to market the event and eventually attract a lot of participants or visitors. This is one of the main targets or goals of the event. At the same time, the social media used can also be affected by insights arising from the upload of social media content related to the event so that engagement is increased. The findings underline the importance of sustained interaction on social media to increase engagement and success in event marketing.